The Pliocene micromammalian fauna from Kanapoi, northwestern Kenya, and its contribution to understanding the environment of Australopithecus anamensis - Manthi, Fredrick Kyalo (Department of Archaeology, 2014)
Includes bibliographical references (leaves 164-202).